THE DEVELOPMENT OF DIGITAL BANKING AND ITS IMPACT ON TRADITIONAL FINANCIAL INSTITUTIONS - Bakoeva Gulbakhor, (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
This article examines the rapid development of digital banking and its impact on traditional financial institutions in the context of global financial transformation. It explores the evolution of digital finance, the rise of fintech companies, and the ways in which technology-driven innovation reshapes customer experiences and bank operations. The paper provides empirical evidence from various economies and discusses the challenges and opportunities that arise from this digital shift. Finally, it highlights the strategic responses of traditional banks, regulatory frameworks, and future trends that will define the financial sector in the digital era.